Occupy the earth global environmental movements - Kedzior, Sya Buryn; Leonard, Liam. (Bingley, U.K. : Emerald, 2014)
The onset of global concerns about environmental risks, climate change and threats to the planet from industry have focused the minds of a generation. Throughout the world, new movements are emerging in an attempt to challenge those who would put profits before the planet. This volume brings together global contributions that represent the cutting edge of research in the area of global environmental movements. Contributions include chapters on the spatial impacts of environmental groups in Israel, the work of Greenpeace in Brazil, environmental activism in Ireland, animal rights and anti-hunt activism in Malta, the global de-growth movement, environmental movement mobilization in China, and anti-pollution activism in India. The scope and breath of this research indicates the emergence of both a global grassroots environmental mobilization in addition to analysis and documentation of these responses by researchers world-wide. With increased threats from climatic change and ecological degradation being highlighted as a threat to much of the world's population in the coming century, this activism and ensuing research becomes all the more significant.
One global movement, many local voices : discourse(s) of the global anti-fracking movement / Tamara Steger, Milos Milicevic -- Japan's evolving civic environmentalism / Robert J. Mason -- Environmental protest in Ireland / Liam Leonard -- Locating environmental knowledge in antipollution movements of Northern India / Sya Buryn Kedzior -- The Mayangna resolve to save the rainforest, their homelands / Nan Marie Greer -- Environmental campaigns in Israel and their spatial impacts / Benny Furst -- Exploring ideology as a 'resource' for environmental justice activism : reflections from the anti-GMO movement in France / Darren McCauley -- The art of contestation and legitimacy : environment, customary communities, and activism in Indonesia / Keith Bettinger, Micah Fisher, Wendy Miles -- From disparate action to collective mobilization : collective action frames and the Canadian food movement / Rebecca Schiff, Charles Z. Levkoe -- Implications of the environmental justice movement on the redistributive urban politics : an example from megacity Dhaka, Bangladesh / Saleh Ahmed -- Spiritual ecology as an international environmental movement / Leslie E. Sponsel -- Bird hunting in European Malta : a case of ENGO empowerment? / Michael Briguglio.
Print version record
Keywords: Science -- Environmental Science; Nature -- Environmental Conservation & Protection; Social impact of environmental issues; Management of land & natural resources; Climatic changes -- Social aspects